Benign recurrent intrahepatic cholestasis--25 years of follow-up. Issue 738 (April 1987) - Putterman, C.; Keidar, S.; Brook, J. G.
Abstract : Only 70 cases of recurrent intrahepatic cholestasis have been reported in the literature since the original description of this entity in 1959. The benign nature of the disease has been questioned, some authors suggesting progression to biliary cirrhosis. We report our follow-up of one such patient for over 25 years with no adverse physical consequences or histological deterioration. Sequential liver biopsies were obtained during this period. A conservative approach to diagnosis and treatment is therefore indicated.